2008
DOI: 10.1002/ijc.23979
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a glycine N‐methyltransferase gene knockout mouse model for hepatocellular carcinoma: Implications of the gender disparity in liver cancer susceptibility

Abstract: Hepatocellular carcinoma (HCC) is the fifth common cancer in the world and it mainly occurs in men. Glycine N-methyltransferase (GNMT) participates in one-carbon metabolism and affects DNA methylation by regulating the ratio of S-adenosylmethionine to S-adenosylhomocystine. Previously, we described that the expression of GNMT was diminished in human HCC. Here, we showed that 50% (3/6) male and 100% (7/7) female Gnmt2/2 mice developed HCC, and their mean ages of HCC development were 17 and 16.5 months, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
102
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 40 publications
1
102
0
1
Order By: Relevance
“…In this study, we showed that Gnmt -/-mice had signs of hepatic steatosis with increased cholesterol deposition in liver tissues, as well as inflammatory infiltration before HCC formation ( Figure 1). According to our previous report, 50% male and 100% female Gnmt -/-mice developed HCC spontaneously (26), suggesting that loss of GNMT is associated with gender disparity of liver cancer susceptibility. It is important to note that the percentages of female Gnmt -/-mice with fatty change were higher than in male Gnmt -/-mice at 11 wks and 9 months (Supplementary Table 5).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In this study, we showed that Gnmt -/-mice had signs of hepatic steatosis with increased cholesterol deposition in liver tissues, as well as inflammatory infiltration before HCC formation ( Figure 1). According to our previous report, 50% male and 100% female Gnmt -/-mice developed HCC spontaneously (26), suggesting that loss of GNMT is associated with gender disparity of liver cancer susceptibility. It is important to note that the percentages of female Gnmt -/-mice with fatty change were higher than in male Gnmt -/-mice at 11 wks and 9 months (Supplementary Table 5).…”
Section: Discussionmentioning
confidence: 87%
“…According to genotypic analyses, the loss of heterozygosity at the GNMT locus in paired tumor and tumor-adjacent tissues from HCC patients ranges from 36% to 47% (24). Previously, we generated a GNMT knockout (Gnmt -/-) mice and reported on their tendencies toward chronic hepatitis, glycogen storage, hypercholesterolemia, fatty nodules and HCC (25,26). In this study, we showed that Gnmt -/-mice impaired cholesterol metabolism and developed steatohepatitis.…”
Section: Glycine N-methyltransferase Deficiency Affects Niemann-pick mentioning
confidence: 77%
See 1 more Smart Citation
“…Then, after our discovery of HCC in our GNMT-/-animals, the Chen group found that their GNMT-/-animals also developed HCC at about 17 months of age. 4 Most surprising in Dr. Chen's letter is the contention that our GNMT knockout mouse is not a complete knockout based on the dubious designation of a 51-nucleotide to 52-nucleotide sequence as a gene "promoter" with no documentation to justify this. They contend that our mouse model generates a protein truncated by 73 amino acids.…”
mentioning
confidence: 99%
“…We know from both the Botnia and Malmö feasibility studies that the best clinical predictors for future diabetes are current smoking status; family history of diabetes, hypertension, and increased body mass index (BMI); and increased triglyceride, apolipoprotein A-I, and liver enzyme levels. 2,3,4 In the baseline patient characteristics, we could only find triglyceride, baseline liver enzyme levels, baseline hyper-…”
mentioning
confidence: 99%